Pemecahan Masalah Matematika Siswa Al-Fityan School Gowa ditinjau dari Gender - Andi Aras; Sartika Arifin; Fawziah Zahrawati B (LPPM IAIN Parepare, 2019)
Problem solving is the highest level of thinking which students need in learning mathematics. This study aims to describe students' mathematical problem solving abilities in terms of gender’s perspective. The research subjects consisted of four students of Class X at SMAIT Al-Fityan School Gowa in the 2018/2019 academic year, consisting of two male students and two female students. The research phase begins with the selection of research subjects determined based on equivalent problem solving ability tests. After selecting the subject, the next phase is giving assignment problem solving, quadratic equations, and interviews. The validity of the data is done by using triangulation of sources by twice interviews, giving tests to students who are different but have the same ability and the same sex in order to produce consistent data. The results showed that female students had better mathematical problem-solving abilities compared to male students based on Polya Steps: 1) understanding the problem, 2) planning the solution, 3) solving the problem, and 4) looking back at the answers.